Existence Center for Sports Performance (SPPOI) in Treatment Sports Injuries - Nurhidayat, N; Sistiasih, Vera Septi; Harjanto, Marvian Dwi (Universitas Muhammadiyah Surakarta, 2019)
Purpose: To find out a) the existence of SPPOI Jakarta as a sports medicine center. Challenges the role of SPPOI in handling national athlete injuries. The role of SPPOI in supporting national sports achievements.Methodology: Research is a qualitative descriptive study with. The subject of this research is the existence of SPPOI Jakarta as a center for sports medicine in its role in supporting national sports achievements.Data collection techniques such as observation, in-depth interviews and recording documentation. Results: The existence of the Jakarta SPPOI as a health center in carrying out the role of education, spreading or instilling or sharing the important principle of paying attention to aspects of injury prevention. SPPOI is a sports clinical clinic with a private status in collaboration with the Ministry of Youth and Sports, The clinic is under the auspices of the Ministry of Youth and Sports which also manages the Indonesian Basketball Academy. With CEO Dr. Andi Kurniawan, SP.KO, Operations Manager Diding Winardi, S.Pd and medical manager Dr. Angelica Anggunadi, Sp.KO. The function of SPPOI is as a health service provider especially in sports medicine. The reality of handling sports injuries at SPPOI and national athletes who have been handled by SPPOI include Anthony SiniSuka Ginting. While Anthony SiniSuka Ginting suffered a knee injury. As a form of SPPOI’s role in supporting national sports achievements SPPOI carries out the role of handling the Asian Games Team as a sports medicine center to handle athlete injuries.Applications/Originality/Value: SPPOI performs its role in supporting the achievements of national athletes in taking preventive, curative, and rehabilitative measures that athletes if in an injury condition the athlete will not be able to compete or can get a high performance program. as a basis for making training programs like athletes do in general.